2005
DOI: 10.1002/pi.1924
|View full text |Cite
|
Sign up to set email alerts
|

2,6‐Diamino‐4‐phenylphenol (DAPP) copolymerized polyimides: synthesis and characterization

Abstract: Novel soluble copolyimides containing phenyl and hydroxyl pendant groups were synthesized from pyromellitic dianhydride (PMDA) and two diamines, 2,6-diamino-4-phenylphenol (DAPP) and 4,4 -oxydianiline (ODA), in various ratios via thermal imidization. The structures and physical properties of the copolyimides were characterized by FTIR, elemental analysis, DSC, dynamic mechanical analysis (DMA), TGA, a universal testing machine for stress-strain behaviour, and a dielectric analyzer to study the effect of DAPP o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…However, owing to the instability of poly(amic acid)s and the liberation of water in the imidization process, problems can arise. Extensive research has been recently carried out to improve the solubility of polyimides and successful examples involve the incorporation of fluorine moieties, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] bulky side groups, [18][19][20][21][22][23][24] alicyclic structure, 25 spiro structure, 26 cardo groups, 27,28 pyridine moiety, 29,30 porphyrin moiety, 31 acridine moiety, 32 and sulfonated structure, [33][34][35][36] and the applications include the functional materials such as low-k material, 3,14,15,25 colorless or light-colored polyimides, 9,10,12 gas transport membranes, 16,17,24 electrochromism materials, 22 pervaporation membranes, 7 materials for organic light-emitting diode (OLED), 27,…”
mentioning
confidence: 99%
“…However, owing to the instability of poly(amic acid)s and the liberation of water in the imidization process, problems can arise. Extensive research has been recently carried out to improve the solubility of polyimides and successful examples involve the incorporation of fluorine moieties, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] bulky side groups, [18][19][20][21][22][23][24] alicyclic structure, 25 spiro structure, 26 cardo groups, 27,28 pyridine moiety, 29,30 porphyrin moiety, 31 acridine moiety, 32 and sulfonated structure, [33][34][35][36] and the applications include the functional materials such as low-k material, 3,14,15,25 colorless or light-colored polyimides, 9,10,12 gas transport membranes, 16,17,24 electrochromism materials, 22 pervaporation membranes, 7 materials for organic light-emitting diode (OLED), 27,…”
mentioning
confidence: 99%
“…While in Figure 2 of magnetic polyimide, the two absorption bands mentioned above almost disappeared, and many characteristic absorption bands of polyimide occur. Where the characteristic imide group absorptions at 1778 and 1714 cm −1 (imide carbonyl asymmetrical and symmetrical stretching), at 1370 cm −1 (CN stretching), and at 721 cm −1 (CN bending) were evident 16, 17. The characteristic absorption of the amide carbonyl at 1650 cm −1 did not appear in the spectrum of the imidize sample, which revealed that the imidization reaction was complete.…”
Section: Resultsmentioning
confidence: 99%
“…To improve the thermal, mechanical and dielectric properties of these two important PEIs with different diamines, mPDA and pPDA, we had studied the preparation of hybrid nanocomposites of PEI by the sol-gel process [4]. The dielectric constants for most PEI films are ~3.5 [5]. To reduce the dielectric constant, researchers have utilized fluorine-containing compounds [6][7], prepared hybrid nanocomposites by adding silica [8][9], or introduced voids into polymer film to take advantage of the low dielectric constant of air [10].…”
Section: Introductionmentioning
confidence: 99%